A hierarchically assembled mesoporous ZnO hemisphere array and hollow microspheres for photocatalytic membrane water filtration - Pan, Jia Hong (2013)
A mesoporous ZnO hemisphere array has been prepared via a topotactic transition of Zn4(OH)6CO3·H2O (ZCHH) by chemical bath deposition. Each hemisphere is comprised of a radially oriented nanoflake shell grown on the hemispherical interior. Reaction time-dependent SEM analysis shows that the morphological formation of ZCHH involves a deposition–growth–secondary growth–redeposition procedure. Upon calcination, ZCHH readily decomposes to nanocrystalline wurtzite-phase ZnO without significant change in morphology, and the release of CO2 and H2O from ZCHH creates an additional mesoporous structure in both hemispherical interior and nanoflake shell. A similar process but without using a substrate has been developed for synthesis of mesoporous ZnO hollow microspheres in powder form. Both the elaborated superstructured photocatalysts consisting of mesoporous nanoflakes have been demonstrated to exhibit excellent performances in the photocatalytic membrane filtration.